Comparison of Diagnostic Accuracy of MRI with and Without Contrast in Diagnosis of Traumatic Spinal Cord Injuries. Issue 43 (October 2015) - Ghasemi, Ahmad; Haddadi, Kaveh; Shad, Ali Ahmadi
Abstract : Abstract: Acute spinal cord injury (SCI) is one of the most common causes of severe disability and mortality after trauma. Magnetic resonance imaging (MRI) can identify different levels of SCI, but sometimes unable to detect the associated soft tissue injuries. The role of MRI with contrast in patients with SCI has not been studied. This is the first study in human to compare the efficacy of MRI with and without contrast in diagnosis and prognosis evaluation of SCIs. In this cross-sectional diagnostic study, MRI with and without contrast was performed on 40 patients with acute spinal injury. In these patients, 3 different types of MRI signal patterns were detected and compared. The most common cases of spinal injuries were accident (72.5%) and the after fall (27.5%). The prevalence of lesions detected includes spine fracture (70%), spinal stenosis (32.5%), soft tissue injuries (30%), and tearing of the spinal cord (2.5%). A classification was developed using 3 patterns of SCIs. Type I, seen in 2 (5.0%) of the patients, demonstrated a decreased signal intensity consistent with acute intraspinal hemorrhage. Type II, seen in 8 (20.0%) of the patients, demonstrated a bright signal intensity consistent with acute cord edema. Type III, seen in 1 (2.5%) of the patients, demonstrated a mixed signal of hypointensity centrally and hyperintensity peripherally consistent with contusion. In the diagnosis of all injuries, MRI with contrast efficacy comparable to noncontrast MRI, except in the diagnosis of soft tissue, which was significantly higher sensitivity ( P < 0.05). So given that is not significant differences between noncontrast and contrast-enhanced MRI in the diagnosis of major injuries (hematoma, edema, etc.) and contrast-enhanced MRI just better in soft tissues. We recommend to the MRI with contrast only used in cases of suspected severe soft tissue injury, which have been ignored by detection MRI without contrast.